Autonomous time and phase calibration of spaceborne bistatic SAR systems - Rodriguez-Cassola, Marc; Prats-Iraola, Pau; López-Dekker, Paco; Reigber, Andreas; Krieger, Gerhard; Moreira, Alberto (European Conference on Synthetic Aperture Radar (EUSAR), 2014)
Bistatic and multistatic SAR constellations offer increased performance at the expense of increased operational complexity. Due to geometric or cost constraints, multistatic SAR constellations might be forced to operate in a partially cooperative manner, i.e., without a direct synchronisation link. In demanding scenarios, like high-resolution bistatic SAR imaging or cross-platform SAR interferometry or tomography, the data need undergo a calibration step to compensate the lack of synchronisation between transmitter and receiver master clocks. Autonomous synchronisation, based on the inversion of the phase and positioning errors of the bistatic SAR images caused by the lack of synchronisation, is used to calibrate the time and phase references of the system with the sole help of the received radar data, which drastically reduces the requirements on the hardware of the system.
DLR Import::2019-04-03